Antioxidant Activity of Red Fruit Juice (Pandanus conoideus L.) Using the CUPRAC Method - Arifin, Marina; Pratama, Mamat; Fawwaz, Muammar; Aminah, Aminah (Pharmaceutical Reports, 2025)
Red fruit (Pandanus conoideus Lam.), which belongs to the Pandanaceae family, is widely used by local Papuan people as a source of food, natural dyes, and traditional medicinal ingredients. Red fruit contains several compounds such as tannins, vitamin C, beta carotene, and flavonoids. This research aims to determine the presence of antioxidant activity using the Cupric Ion Reducing Antioxidant Capacity (CUPRAC) method. Antioxidant capacity using the CUPRAC method is expressed as mg of ascorbic acid equivalent (AAE) per g of juice (mgAAE/g). The method is measured using a UV-Vis spectrophotometer with the maximum wavelength. Ascorbic acid was used as a comparison to assess the antioxidant ability of red fruit juice. The results showed that the antioxidant activity capacity of red fruit juice was 100.4 mgAAE/g. Thus, red fruit can be developed as a natural antioxidant.